2023
DOI: 10.1101/2023.06.10.23291206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV self-testing positivity rate and linkage to confirmatory testing and care: a telephone survey in Côte d’Ivoire, Mali, and Senegal

Abstract: HIV self-testing (HIVST) empowers individuals by allowing them to decide when and where to test and with whom to share their results. From 2019 to 2022, the ATLAS program distributed ≈ 400 000 HIVST kits in Côte d Ivoire, Mali, and Senegal. It prioritised key populations, including female sex workers and men who have sex with men, and encouraged secondary distribution of HIVST to their partners, peers and clients. To preserve the confidential nature of HIVST, use of kits and HIVST results were not systematical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…According to STAR data, 80% of the distributed test kits were used [28]. An anonymous phone‐based ATLAS survey suggested that 50% of individuals with reactive HIVST results proceed to confirmatory testing and, if confirmed HIV positive, will be linked to care [29,30]. Those who did not proceed to confirmatory testing may be picked up again by HTS and retested in the future.…”
Section: Methodsmentioning
confidence: 99%
“…According to STAR data, 80% of the distributed test kits were used [28]. An anonymous phone‐based ATLAS survey suggested that 50% of individuals with reactive HIVST results proceed to confirmatory testing and, if confirmed HIV positive, will be linked to care [29,30]. Those who did not proceed to confirmatory testing may be picked up again by HTS and retested in the future.…”
Section: Methodsmentioning
confidence: 99%